MANAGING INFORMATION AND INFORMATION FLOWS WITHIN ORGANS; INTERNAL AND EXTERNAL COMMUNICATION PROFESSIONAL SETTINGS - Florence, Kenebara (Acta Scientiae et Intellectus, 2024)
An organization consists of a group of people who work together to achieve a common purpose. It can consist of two people or two million people, and can be structured as a small business or an army, corporation, government or church. An organization is bigger than the individuals and groups that comprise it, but smaller than the society that gives it its context and environment. The work of managers in small and medium-sized enterprises is very information-intensive and the environment in which it is done is very information rich. But are managers able to exploit the wealth of information which surrounds them? And how can information be managed in organizations so that its potential for improving business performance and enhancing the competitiveness of these enterprises can be realized? Answers to these questions lie in clarifying the context of the practice of information management by exploring aspects of organizations and managerial work and in exploring the nature of information at the level of the organization and the individual manager. From these answers it is possible to suggest some guidelines for managing the integration of business strategy and information, the adoption of a broadly-based definition of information and the development of information capabilities. Information sharing is critical to an organization’s competitiveness and requires a free flow of information among members if the organization is to remain competitive.